Mentawaian and their land: local tenurial system, regional development, and cash economy - Amien Tohari (JPW (Jurnal Politik Walisongo), 2022)
This article discusses the agrarian problems that will occur in Mentawai due to the encounter between the local tenure system and modern development. In many local development planning documents, the underlying development logic is to integrate social into the cash economy or market economy. Most of this modern development does not clearly describe the processes of social change that have taken place. In communities that still practice traditional economics, this kind of development has a very significant impact on changing social relations. This paper shows that development that changes the tenure system of a society, whether intentional or not, slowly or quickly, will also change the cultural system, political system, and social structure of society. The Mentawai people will learn how to live and survive in the new system. Some of them may be successful, and many of them will be eliminated. Besides, a shift in the management of natural resources, and land, which is different from the previous one will give rise to a wider agrarian conflict and transformation.